Collaborative Channel Sensing Under S-Aloha for IoT Based CRSN - Janani, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
To reinforce the expected technological advancement of the Internet of Things (IoT) systems, a highly available, robust, and accessible communication technology will be required. Narrowband-IoT (NB-IoT) is one such radio-based technology developed to connect and control low-power autonomous devices. It is anticipated to concur with the presently used legacy Long-Term Evolution (LTE) standards as well as the imminent fifth-generation communication technologies. The key objective of NB-IoT is to enable immense machine-to-machine (M2M) communication among IoT devices that require low-power, low-throughput, and extended battery life. However, the bandwidth allocation for this technology is restricted between 180 kHz and 200 kHz and is not adequate to handle the explosive growth and development of the number of deployed devices in the NB-IoT systems. Besides, in an attempt to increase the coverage in the NB-IoT network, recent research studies have introduced the notion of retransmission. Since repeated transmissions guarantee coverage improvement but lead to radio resource wastage, the conventional bandwidth distribution techniques are not appropriate for the NB-IoT-based communication systems. Motivated by this research gap we integrate cognitive radio technology and NB-IoT to form Narrowband Cognitive IoT (NBC-IoT) network and we develop an Enhanced Random Access Protocol (ERAP) for this network. Our proposed ERAP exploits (i) a collaborative channel sensing technique to enhance the system throughput; and (ii) a collision-free reporting with dynamic admission control strategy to enable robust communication against packet collisions. The proposed protocol is implemented and its achievable performance is evaluated using the NS2 simulator. Numerical simulation results demonstrate that our proposed protocol considerably outdoes two existing protocols such as normal routing of IoT and slotted-ALOHA in terms of performance measures including throughput, packet delivery ratio, communication cost, transmission latency, and energy consumption.